2010
DOI: 10.1007/978-3-642-11250-8_88
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results on a Virtual Observatory Search for Companions to Luyten stars

Abstract: The Aladin sky atlas of the Virtual Observatory has shown to be a powerful and easy-handling tool for the discovery, confirmation, and characterisation of high proper-motion, multiple stellar systems of large separation in the solar vicinity. Some of these systems have very low mass components (at the star/brown dwarf boundary) and are amongst the least bound systems found to date. With projected physical separations of up to tens of thousands astronomical units, these systems represent a challenge for theoret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…First, a physical size must be chosen for the XYZ spatial part of the host-star model. Here, we decided to use a model with a characteristic width of 0.1 pc, corresponding to physical separations of about 20,600 au, larger than some of the widest-separation binaries known to be at least lightly gravitationally bound (Caballero et al 2012;Deacon et al 2014;Marocco et al 2020). This choice for the spatial size of the model should therefore be applicable to systems out to the extreme edge of known bound companions.…”
Section: Chance Alignment Probabilitymentioning
confidence: 99%
“…First, a physical size must be chosen for the XYZ spatial part of the host-star model. Here, we decided to use a model with a characteristic width of 0.1 pc, corresponding to physical separations of about 20,600 au, larger than some of the widest-separation binaries known to be at least lightly gravitationally bound (Caballero et al 2012;Deacon et al 2014;Marocco et al 2020). This choice for the spatial size of the model should therefore be applicable to systems out to the extreme edge of known bound companions.…”
Section: Chance Alignment Probabilitymentioning
confidence: 99%
“…Using archived surveys along with state-of-the-art follow-up observations enables the combination of different data sources (Caballero et al 2010;Alonso-Floriano et al 2011), offers a way for accurate indirect determinations of quantities like parallax (Gould & Chanamé 2004) or the evolutionary status (Makarov et al 2008), and provides a starting point for extended surveys (like the Palomar/Keck survey of Metchev & Hillenbrand 2009), as well as extreme findings (like the wide ultra-cool binary by Caballero 2007).…”
Section: Multiplicitymentioning
confidence: 99%
“…Four years before, at the VIII SEA meeting in Santander, he gave two talks: one on formation, evolution and multiplicity of brown dwarfs and giant exoplanets (Caballero 2010a), the other on a Virtual Observatory search for companions to Luyten stars in close collaboration with some of the authors of this proceeding. There, Caballero et al (2010a) showed preliminary results of an Aladin-based survey for companions to high-proper-motion Luyten stars in the Salim & Gould (2003) catalogue. Among the 1947 studied stars (and white dwarfs) with proper motions in the interval 0.5 < µ < 1.0 arcsec a −1 (see Fig.…”
Section: July 2008: Proper-motion Companions To Luyten Starsmentioning
confidence: 99%